2021
DOI: 10.3390/ijerph182111581
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Healthcare Workers Amid the COVID-19 Pandemic: A Follow-Up Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has posed a significant challenge to the modern healthcare system and led to increased burnout among healthcare workers (HCWs). We previously reported that HCWs who engaged in COVID-19 patient care had a significantly higher prevalence of burnout (50.0%) than those who did not in November 2020 (period 1). We performed follow-up surveys in HCWs in a Japanese national university hospital, including basic demographics, whether a participant engaged in care of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…Participants in this study revealed high levels of occupational fatigue, poor inter-shift recovery and loneliness while at work. There is evidence validating the cumulative negative impact from the subsequent waves of the pandemic as well ( Nishimura et al 2021a , 2021b ; Tan et al 2020 ), which align with our findings. Additionally, participants in the study explained how the lack of social interaction with colleagues made work feel more arduous and lonelier.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Participants in this study revealed high levels of occupational fatigue, poor inter-shift recovery and loneliness while at work. There is evidence validating the cumulative negative impact from the subsequent waves of the pandemic as well ( Nishimura et al 2021a , 2021b ; Tan et al 2020 ), which align with our findings. Additionally, participants in the study explained how the lack of social interaction with colleagues made work feel more arduous and lonelier.…”
Section: Discussionsupporting
confidence: 90%
“…Studies that explored HCPs during the second and third waves reveal no abatement of psychological burden or burnout in HCPs ( Gonçalves et al 2021 ; Nishimura et al 2021a , 2021b ; Tan et al 2020 ). There is growing concern that the protracted crisis may cause lasting harm to HCPs and the health system ( Greenberg and Raferty 2021 ; Lorente et al 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“…There was a large spectrum of coping, with some participants remaining relatively unaffected while others were undoubtedly struggling. Previous studies have noted decreasing morale, adverse mental health consequences, and individual differences in coping in healthcare staff globally during the pandemic, 3 , 33 , 34 indicating these findings are not unique to palliative care in Scotland. Vulnerability is an important point here and is considered part of the human condition, yet as Kottow 35 argues may be better replaced with the term susceptibility.…”
Section: Discussionmentioning
confidence: 84%
“…Nesse contexto, o estresse e a SB tornaram-se ainda mais pronunciados nos profissionais de saúde que estão atuando na linha de frente da batalha contra o avanço da Covid-19, por estar diretamente ligados aos diferentes estressores ocupacionais. Dentre os estressores identificados por pesquisadores, podemos-se citar as longas jornadas de trabalho, a falta de profissionais ou pessoas capacitadas, a falta de reconhecimento profissional, a exposição do profissional a riscos químicos e físicos, assim como o contato constante com o sofrimento, a dor e a morte (BRERA et al, 2021;KANNAMPALLIL et al, 2020;NISHIMURA et al, 2021).…”
Section: Métodounclassified